Revolução Mexicana e imprensa operária brasileira: leitura libertária e circulação de idéias - SOUSA, Fábio da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Neste artigo, apresentaremos os principais pontos de minha dissertação de mestrado em andamento, intitulada “Operários e Camponeses. A repercussão da Revolução Mexicana na Imprensa Operária Brasileira (1910-1920)”. Por meio de uma leitura crítica das matérias jornalísticas sobre a Revolução do México que foram publicadas em periódicos da imprensa operária brasileira, no decênio de 1910 até 1920, pretendemos investigar e compreender o impacto desse acontecimento na embrionária classe operária brasileira no início do século XX.

In this article it will be presented the main topics of the ongoing dissertation, entitled “Factory and Farm Workers. The repercussion of the Mexican Revolution in the Brazilian Workers’ Press (1910-1920)”. Through a critical reading of the texts published about the Mexican Revolution in Brazilian journals from 1910 to 1920, our main aim is to investigate and comprehend the impact of this historical event on the rising Brazilian factory workers, as a class, in the beginning of the XXth Century.
Mexican revolution and press brazilian workers: libertarian reading and movement of ideas
Keywords: Mexican Revolution; Workers’ Press; Brazil and Mexico; Revolução Mexicana; Imprensa Operária; Brasil e México